1999
DOI: 10.1046/j.1365-2486.1999.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2and plant structure: a review

Abstract: Summary Consequences of increasing atmospheric CO2 concentration on plant structure, an important determinant of physiological and competitive success, have not received sufficient attention in the literature. Understanding how increasing carbon input will influence plant developmental processes, and resultant form, will help bridge the gap between physiological response and ecosystem level phenomena. Growth in elevated CO2 alters plant structure through its effects on both primary and secondary meristems of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
283
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(312 citation statements)
references
References 154 publications
(253 reference statements)
22
283
2
5
Order By: Relevance
“…increasing the root-to-shoot ratio (Ceulemans and Mousseau, 1994;Rogers et al, 1996;Pritchard et al, 1999;Rogers et al, 1999). However, some studies reported decreased rootto-shoot ratio (Salsman et al,1999;McMaster et al, 1999) in response to high [CO 2 ] while others did not observe any significant effect (Mo et al, 1992;Ferris and Taylor, 1993;Chaudhuri et al,1990;Obrist and Arnone, 2003).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…increasing the root-to-shoot ratio (Ceulemans and Mousseau, 1994;Rogers et al, 1996;Pritchard et al, 1999;Rogers et al, 1999). However, some studies reported decreased rootto-shoot ratio (Salsman et al,1999;McMaster et al, 1999) in response to high [CO 2 ] while others did not observe any significant effect (Mo et al, 1992;Ferris and Taylor, 1993;Chaudhuri et al,1990;Obrist and Arnone, 2003).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In general, elevated CO 2 has been found to increase primary production, unless other resources were limiting (Saxe et al ., 1998;Körner, 2003), and to shift plant resource allocation towards the roots, whereas elevated O 3 diminished net carbon uptake and typically reduced root rather than shoot growth (Andersen, 2003). In addition, elevated CO 2 and O 3 regimes were found to induce changes in crown and root architecture because of modification of branching patterns (Pritchard et al ., 1999;Dickson et al ., 2001). Hence, elevated CO 2 and O 3 were used as stressors to provoke differential changes in growth and allocation between settings of intra-and inter-specific competition in order to more readily distinguish relevant mechanisms in tree competitiveness (Grams et al ., 2002;Matyssek et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is still unknown whether forests of the future will maintain a higher leaf area index (LAI), as implied from smalltree studies (Ceulemans et al, 1997) or whether the long-term (decades) responses will be reduced allocation to foliage and lower LAI, as suggested by some modeling approaches (Medlyn and Dewar, 1996) or involve acclimation to limited nitrogen (Oren et al, 2001). Leaf growth is often stimulated in short-term response to elevated [CO 2 ] (Taylor et al, 1994;Pritchard et al, 1999), and both leaf cell expansion and cell production are sensitive to [CO 2 ] (Taylor et al, 1994). It is likely that these processes respond to additional carbohydrate from photosynthesis and, as such, altered atmospheric [CO 2 ] provides a critical insight into how carbon regulates plant development and growth (Masle, 2000).…”
mentioning
confidence: 99%
“…Leaf growth is often stimulated in short-term response to elevated [CO 2 ] (Taylor et al, 1994;Pritchard et al, 1999), and both leaf cell expansion and cell production are sensitive to [CO 2 ] (Taylor et al, 1994). It is likely that these processes respond to additional carbohydrate from photosynthesis and, as such, altered atmospheric [CO 2 ] provides a critical insight into how carbon regulates plant development and growth (Masle, 2000).…”
mentioning
confidence: 99%